Fermi‐level pinning by carrier com‐ pensating midgap donor defect band in homoepitaxially grown p‐type ZnO by MBE. Issue 7 (31st March 2014) - Masamoto, T.; Noda, K.; Maejima, T.; Natsume, R.; Matsuo, T.; Akiyama, A.; Yukue, T.; Hiroe, S.; Abe, T.; Kasada, H.; Harada, Y.; Ando, K.
Abstract: We have performed homoepitaxial MBE growth of nitrogen (N) ‐doped ZnO and studied the postanneal effect on electrical conduction properties. A rapid postanneal after MBE growth is found to enhance the donor–acceptor (D–A) pair emission intensity, converting from n‐type (as‐grown) to p‐type conduction. The p‐type ZnO showed extremely high resistivity (>10 3 Ω cm) at room temperature. Carrier‐compensating donor‐like defects in N‐doped ZnO were traced by using PPC (persistent photocurrent), which is coupled with in situ Hall effect measurements. It is found that highly resistive p‐ZnO includes a high density of metastable donor‐like defects forming a deep donor band in the midgap region. This midgap donor band plays a role in Fermi‐level pinning at around the midgap position, resulting in high resistivity. Based on X‐ray photoemission spectroscopy experiments one possible origin of the deep donor band is introduced as nitrogen molecule (N2(o) ) defects locating at the O atomic site. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)